The Japanese respiratory society guidelines for the management of cough and sputum (digest edition) - Mukae, Hiroshi; Kaneko, Takeshi; Obase, Yasushi; Shinkai, Masaharu; Katsunuma, Toshio; Takeyama, Kiyoshi; Terada, Jiro; Niimi, Akio; Matsuse, Hiroto; Yatera, Kazuhiro; Yamamoto, Yoshihiro; Azuma, Arata; et al. (Respiratory investigation, 2021)
Cough and sputum are common complaints at outpatient visits. In this digest version, we provide a general overview of these two symptoms and discuss the management of acute (up to three weeks) and prolonged/chronic cough (longer than three weeks). Flowcharts are provided, along with a step-by-step explanation of their diagnosis and management. Most cases of acute cough are due to an infection. In chronic respiratory illness, a cough could be a symptom of a respiratory infection such as pulmonary tuberculosis, malignancy such as a pulmonary tumor, asthma, chronic obstructive pulmonary disease, chronic bronchitis, bronchiectasis, drug-induced lung injury, heart failure, nasal sinus disease, sinobronchial syndrome, eosinophilic sinusitis, cough variant asthma (CVA), atopic cough, chronic laryngeal allergy, gastroesophageal reflux (GER), and post-infectious cough. Antibiotics should not be prescribed for over-peak cough but can be considered for atypical infections. The exploration of a single/major cause is recommended for persistent/chronic cough. When sputum is present, a sputum smear/culture (general bacteria, mycobacteria), cytology, cell differentiation, chest computed tomography (CT), and sinus X-ray or CT should be performed. There are two types of rhinosinusitis. Conventional sinusitis and eosinophilic rhinosinusitis present primarily with neutrophilic inflammation and eosinophilic inflammation, respectively. The most common causes of dry cough include CVA, atopic cough/laryngeal allergy (chronic), GER, and post-infectious cough. In the last chapter, future challenges and perspectives are discussed. We hope that the clarification of the pathology of cough hypersensitivity syndrome will lead to further development of “pathology-specific non-specific therapeutic drugs” and provide benefits to patients with chronic refractory cough.